PENGARUH MOTIVASI UNTUK MENGHINDARI RIBA DAN PENGETAHUAN PRODUK TERHADAP KEPUTUSAN MENJADI NASABAH (STUDI KASUS PADA BANK MANDIRI SYARIAH KC MALANG) - Permana, Ade Indra; Prastowo, Sugeng Lubar; Djaenudin, Ernie Mardiany (Universitas Islam Syekh-Yusuf, 2021)
The title in this study is the Effect of Motivation to Avoid Usury and Product Knowledge of the Decision to Become a Customer Case Study at Bank Mandiri Syariah Kc Malang. This study aims to determine and analyze the variables of Avoiding Usury Motivation, Product Knowledge, partially and simultaneously have a significant effect on the decision to become a customer. The method used in this research is to use quantitative descriptive with a sample of 100 people. In this study the sampling technique used was using accidental sampling and in gathering data using questionnaires, while for the test results using the test of validity, reliability, coefficient of relations, classical assumptions and using multiple linear regression. The results of this study indicate that the variables X1, X2 simultaneously or partially have a significant effect on Y where the resulting value is less than 0.05. while for the classic assumption test it can be concluded that each variable can be normally distributed and heteroscedasticity does not occur.